ANALISIS RANTAI PASOK DAN PROFIT MARGIN PEDAGANG TERNAK DOMBA DI KABUPATEN BANYUMAS - Ludy Ikhwanul Jihad; Nunung Noor Hidayat; Yusmi Nur Wakhidati (ANGON: Journal of Animal Science and Technology, 2020)
Background. Research on the Analysis of supply chain and Profit Margin of sheep traders in Banyumas distric Regency was conducted on March 1 to April 1, 2020 in Banyumas district. Research objectives is 1) know the supply chain, profit margins and influence of educational factors, the number of livestock mastery and the length of raising on profit margin. Materials and Methods. The study was conducted using a survey method of sheep in the animal market of Banyumas district. Sample assignment using a snowball sampling of 30 respondents. The data analysis used was descriptive analysis and regression test. Results.The results showed the sheep's livestock traders from their functions and roles were distinguished into mobile collecting traders and collecting traders. The activity of traders to form a sales chain for sheep is divided into two marketing patterns, namely marketing pattern one involving breeders, mobile collecting traders and consumers and marketing two pattern involving breeders, mobile collecting traders, collecting traders and consumers. Average marketing cost Rp 94,267, average price of sheep buy Rp 4,560,000, average total cost of Rp 4,654,267, average sheep's acceptance Rp 5,041,500, the average income of sheep traders Rp 387,233 in one day market and profit margin for marketing agensi one is 9,41 percent and marketing agency two is 6,61 percent. Conclusion. The variables that affect the profit margin of sheep traders in Banyumas district are the education level, amount of livestock mastery and marketing agency.